Superando desafios técnicos: um roteiro de exercícios preparatórios para a performance do primeiro movimento do Concerto para Violino em Lá Menor - Op.53, de Antonín Dvorák - Lucas Barreto Ferreira (2020)
Proposal of a preparatory exercises guide in order to overcome technical and musical difficulties on selected excerpts from the first movement of A. Dvorák’s Concerto in A Minor Op.53 for Violin and Orchestra. The main model used were the exercises created by Maxim Jacobsen in his method Mendelssohn Violin-Konzert Op.64, E moll: 24 Vorbereitende Ubungen. In order to complement Jacobsen’s model, we used the works by Ivan Galamian, Robert Gerle and Simon Fischer. An analysis of the technical elements used by these authors was the basis to elaborate similar exercises specifically for selected excerpts from Dvorák`s Concerto according to their technical and musical difficulties: intonation in arpeggios with changing of position, intonation and fluency in passages with double stops, passages in arpeggiated chords, long scale-like and arpeggiated passages, and passages in sequences of chords.